Hungary : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2004)
This 2004 Article IV Consultation states that Hungary's entry into the European Union comes on the heels of impressive accomplishments. Its successes were based on the long-lasting effects of significant structural reforms and privatization during the 1990s, which also facilitated Hungary's outward orientation, foreign direct investment inflows, strong export performance, flexible labor and product markets, and sound banking system. The success was also rooted in undertaking macroeconomic adjustment measures when needed, and in maintaining an adequate level of international competitiveness.